Common Surgical Diseases An Algorithmic Approach to Problem Solving - Saclarides, Theodore J.; Myers, Jonathan A.; Millikan, Keith W. (Springer New York : Imprint: Springer, 2015)
Written by leaders in the field, the third edition of Common Surgical Diseases: An Algorithmic Approach to Problem Solving, provides surgical residents and medical students with a current, concise and algorithmic approach to frequently encountered clinical challenges. Each chapter details every common surgical disease in the form of a succinct text coupled with step-by-step algorithm. It also walks the reader through the evaluation, diagnosis, treatment and follow-up of the most common surgical problems. Thoroughly updated and revised, the third edition focuses on problems most frequently encountered by general surgeons and their residents and students. More factual information is included in the form of charts and tables for quick and easy reference. The section on critical care is updated and expanded. The section on pre-operative considerations has new chapters on how to best manage patient's medications before surgery (anticoagulants, anti-platelet drugs) and prophylaxis of deep venous thrombosis. Other new chapters include access for hemodialysis, adrenal incidentaloma, esophageal cancer, pancreatic cancer, management of abdominal wall defects, hyperglycemia, necrotizing soft tissue infections and SIRS/sepsis. Especially pertinent in todays' medical environment is an understanding of the genetic component of certain cancers and chapters are devoted to screening and treating patients with genetic predispositions to colorectal and breast cancer.